UTILIZATION OF DAYAK ONION AS HEALTHY SNACKS - Hendy Lesmana; Qur’ani Qur’ani; Dewy Haryanti Parman (International Journal of Nursing and Health Services (IJNHS), 2019)
In Indonesia, there are an estimated 100 to 150 families of plants, and of that number, most of them have the potential to be used as medicinal plants. The traditional medicinal plant that has a function as a medicinal plant, one of them is Dayak onions, where the onions Dayak is very much found in Kalimantan and is believed to have many health benefits. Dayak onions are very rarely found in the form of snacks, so it is fascinating to be used as research material to get a stick made of Dayak onions with the best flavor, delicious, tasty, crispy, and attractive to be consumed by the consumer. Not only are the Dayak onion sticks delicious and tasty, but they also provide many benefits for those who consume them. This research makes a healthy snack product in the form of sticks made from Dayak onions with rice flour mixture. The method used is the method of case study research to find the best results from multiple comparison Dayak onions and rice flour that has been made, namely 1:1, 1:2, and 1:3. The sampling technique in this study used a purposive sampling technique, which is a sampling technique with specific considerations. Results: From the research on Dayak onion stems made several main comparison ingredients, namely Dayak onions and rice flour which get a savory, savory and crispy taste using 1: 2 or the equivalent of 50gr Dayak onions and 100gr rice flour Recommendation: the products produced still need to be developed in various variants such as spicy, salty and sweet so that consumers are more interested in getting them. Keywords: Dayak onion, sticks, traditional food ingredients